Modelamiento y diseño conceptual de la separación de lactato mediante electrodiálisis (2017)
In the research projects carried out by the biotechnology group of the Uiversity of America, a biotechnological route of lactic acid production was carried out from pineapple residues, to lactic acid from the fermented broth. In separating and purifying the product there have been several drawbacks, as the costs of production, environmental consequences and legal limitations have made the extraction with solvents a process of separation of low viability. This project aims to generate knowledge in the application of non-conventional separation techniques using membranes, in the same way, the work can be a fundamental basis for the development of new projects aiming at the design and study of new separation alternatives And purification of lactic acid from a biotechnological route.